2015
DOI: 10.1038/srep13523
|View full text |Cite
|
Sign up to set email alerts
|

Damage evaluation in graphene underlying atomic layer deposition dielectrics

Abstract: Based on micro-Raman spectroscopy (μRS) and X-ray photoelectron spectroscopy (XPS), we study the structural damage incurred in monolayer (1L) and few-layer (FL) graphene subjected to atomic-layer deposition of HfO2 and Al2O3 upon different oxygen plasma power levels. We evaluate the damage level and the influence of the HfO2 thickness on graphene. The results indicate that in the case of Al2O3/graphene, whether 1L or FL graphene is strongly damaged under our process conditions. For the case of HfO2/graphene, μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 54 publications
0
37
0
Order By: Relevance
“…7b . The observed patterns differ completely from that of m-HfO 2 , possibly because of the breakage of crystal symmetry by point defects or edges in c-HfO 2 3 , 32 .
Figure 7 ( a ) XRD patterns, and ( b ) Raman spectra of c-HfO 2 nanostructures; ( c ) UV-vis absorption spectrum with inset depicting Tauc plots for band gaps; ( d ) thermogravimetric analysis (TGA) curves for c-HfO 2 nanostructures.
…”
Section: Resultsmentioning
confidence: 69%
“…7b . The observed patterns differ completely from that of m-HfO 2 , possibly because of the breakage of crystal symmetry by point defects or edges in c-HfO 2 3 , 32 .
Figure 7 ( a ) XRD patterns, and ( b ) Raman spectra of c-HfO 2 nanostructures; ( c ) UV-vis absorption spectrum with inset depicting Tauc plots for band gaps; ( d ) thermogravimetric analysis (TGA) curves for c-HfO 2 nanostructures.
…”
Section: Resultsmentioning
confidence: 69%
“…6b) without affecting the SLG opto-electric performance and avoiding defect formation and/or chemical interactions is another challenge. Plasma assisted dielectric deposition technologies tend to induce defects in SLG [274,275]. The atomic layer deposition (ALD) of high-k dielectrics has been studied [276].…”
Section: Wafer-scale Integrationmentioning
confidence: 99%
“…The D peak intensity remained constant even after the iCVD copolymer film was deposited on the graphene. This revealed that, unlike other deposition processes, the copolymer deposition process did not generate additional defects in the graphene. Figure b,c shows the 2D and G peaks, as well as the 2D/G and G peak changes of the graphene depending on the VIDZ concentration in the copolymer dielectrics, respectively.…”
Section: Resultsmentioning
confidence: 90%